Regulation of neutrophil apoptosis by Mcl-1. (1st June 2004) - Edwards, S.W.; Derouet, M.; Howse, M.; Moots, R.J.
Abstract : Neutrophils rapidly undergo spontaneous apoptosis, but this process can be considerably delayed by exposure to a variety of agents such as pro-inflammatory cytokines. The anti-apoptotic protein of the Bcl-2 family, Mcl-1, plays a key role in the regulation of neutrophil apoptosis. The protein has some unusual properties compared with other family members, including an extremely high turnover rate. Many factors, such as cytokines and local oxygen concentrations, can regulate cellular levels of Mcl-1 via transcription and post-transcriptional modification, control the survival time of neutrophils within tissues and thereby influence the inflammatory response.